Efeitos dos parâmetros de usinagem no acabamento superficial de materiais cerâmicos a verde - Gonçalves Júnior, Marcos [UNESP] (2014)
The machining of green ceramic has benn investigated as a method for manufacturing of complex shapes. Such method provides a possible alternative for manufacturing of ceramic of complex geometry with dimensions close to the final, due to low mechanical strength, presenting advantages in terms of cost-benefit and improvement surface finishing compared to machining performed only after the sintering. In this work, the forces of machining of green ceramic workpiece and analyzed its correlation with the cutting parameters and surface finishing were measured. The correlation between the cutting power and removal rate are important parameters in order to define the project in ceramic products, in which inadequate parameters can produce excessive damage to the work piece surface. The present paper aimed the elaboration and conception of data acquisition system of the machining forces, using a dynamometer three coordinates for monitoring the cutting forces, feed and depth. For this purpose, cylindrical speciments of alumina 99.8% purity were conformed into isostatic press at 200 MPa, being turned with different cutting parameters by three types of cermet tool under machining constant conditions. Efforts were confronted with variables such as finishing and surface roughness, tip radius and wear of the cutting tool and temperature during the machining, registered through a microtermopar inserted next to tip of the cutting tool. The results showed a strong influence of the wear of the cutting tool in increased efforts and surface finish, as well as the radius of the tool tip had influence on surface finishing and in the tool life. If was verified that the depth of cut had no significant effect on the surface quality, being the cutting speed and feed the variables that had greater effect on the finishing. The feed force showed major increase efforts and the force of depth minor increments during the machining. The recorded temperature did not...